2013
DOI: 10.1007/s00401-013-1157-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alzheimer neurodegenerative pathologies and their combinations are more frequent than commonly believed in the elderly brain: a community-based autopsy series

Abstract: Neurodegenerative diseases are characterised by neuronal loss and cerebral deposition of proteins with altered physicochemical properties. The major proteins are amyloid-β (Aβ), tau, α-synuclein, and TDP-43. Although neuropathological studies on elderly individuals have emphasised the importance of mixed pathologies, there have been few observations on the full spectrum of proteinopathies in the ageing brain. During a community-based study we performed comprehensive mapping of neurodegeneration-related protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
270
2
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(305 citation statements)
references
References 93 publications
27
270
2
6
Order By: Relevance
“…In addition to evaluating cases with only AD-type tau pathology, we also pooled cases with different concomitant tau pathologies together, since these cases are more representative of ageing in the human brain [35,36]. We detected a weaker correlation between LGN and occipital pathology.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to evaluating cases with only AD-type tau pathology, we also pooled cases with different concomitant tau pathologies together, since these cases are more representative of ageing in the human brain [35,36]. We detected a weaker correlation between LGN and occipital pathology.…”
Section: Discussionmentioning
confidence: 99%
“…showed Aβ deposits (68.7%), CVLs (48.9%), non-Alzheimer tauopathies (23.2%), TDP proteinopathy (13.3%), and others (inflammation, tumors, etc, 15.1%). Most of these lesions did not increase the probability of the co-occurrence of others, while the number of observed pathologies correlated significantly with AD-neuropathologic changes [289]. A recent cross-sectional study in a community-based sample of 72 cognitively normal older individuals (mean age 74.9 ± 5.7 years) confirmed that a substantial number harbor neurodegeneration without Aβ burden, but association of neurodegenerative lesions with CVD can emerge through non-Aβ pathways within regions most affected by AD [222].…”
mentioning
confidence: 80%
“…), and was over 40% in a large autopsy series of patients over age 80 [270] (Table 4). The burden of vascular and AD type pathologies are considered to be independent of each other, and are consistent with an additive or synergistic effect of both types of lesions on cognitive impairment [147,175,185,272,[286][287][288][289][290][291]. The thresholds for vascular and degenerative lesions in distinguishing "pure" VaD or AD from mixed cases have been discussed [274,292,293].…”
mentioning
confidence: 99%
“…(34) It has even been debated whether subjects with PART represent an early stage of AD or merely reflect a neurodegenerative process at an early stage. (35) Also, "acute or incidental" aS pathology has been reported to be seen in 5% to 31% of the cognitively unimpaired aged subjects (36,37), and Ab has been reported in the cortex of 39% to 82% of cognitively unimpaired aged subjects (38,39). TDP43 pathology has been reported in 3% to 40% of cognitively unimpaired aged subjects.…”
Section: Aging and Nddmentioning
confidence: 99%